Incidental Finding of Annular Pancreas in a Routine Cadaveric Dissection: Case Report - Prasad, Mythraeyee; Kuriakose, Theresa Susan; Rout, Sipra (Journal of Morphological Sciences, 2019)
Annular pancreas is a rare congenital anomaly that results from the malrotation of the ventral pancreatic bud. The presentation of annular pancreas varies: it can be asymptomatic or present clinical symptoms of duodenal obstruction that can affect all age groups, from newborns to adults. In the present case report, we describe a complete type of annular pancreas at the level of the second part of the duodenum, which was an incidental finding in a prosected specimen. This anomaly has significant clinical relevance to clinicians and radiologists due to its variable presentation. The embryological, clinical and radiological aspects of this congenital anomaly are discussed in detail in the present article.
Keywords: annular pancreas; congenital anomaly; duodenal obstruction; pancreatic bud